IMPLEMENTASI RAPID APPLICATION DEVELOPMENT UNTUK MENDIAGNOSIS PENYAKIT DIARE DAN DISENTRI PADA ANAK - Embun Fajar Wati; Enok Tuti Alawiah; Martua Hami Siregar (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
The diagnosis of diarrhea and dysentery diseases, is felt to be almost the same and there is no difference. Diarrhea is a disease that is still common in childhood and even becomes one of the many diseases that cause death in children. Dysentery is a digestive system disorder that occurs due to inflammation of the large intestine which is characterized by abdominal pain and defecation repeatedly and causes the sufferer to lose a lot of fluids. The initial symptoms before consultation with a doctor can be overcome by an expert system that can make conclusions and drug solutions that must be consumed to alleviate them so as to prevent death as well as a fatal result of diarrhea and dysentery. Data collection was carried out with observations from several previous journals relating to the expert system regarding diarrhea and dysentery. While the development method uses RAD (Rapid Application Development). The data analysis method uses forward chaining, which is continuous sequence (asking for symptoms and then concluding). The design uses several UML diagrams including use case and sequence diagrams and use ERD (Entity Relationship Diagram) too. This research is expected to provide appropriate early treatment for children affected by dysentery or diarrhea. For further research, it is hoped that the process of adding a history of diarrhea and dysentery to all patients.